The Relationship of Self-Efficacy Toward Students Achievement Index of Faculty of Teacher Training and Education at Malikussaleh University - Faradhillah, Faradhillah; Hadiya, Izkar; Fatmi, Nuraini (Universitas Malikussaleh, 2020)
This study aims to determine the relationship between Self-Efficacy on Students Achievement Index. This study is a quantitative research type ex post facto. The study sample was determined by proportionate cluster random sampling. Study data consisting of student self-efficacy data and students academic achievement index data were each tested for their homogeneity and normality using SPSS and it was found that the data distribution was normal and homogeneous. Data that has been tested for homogeneity and normality are then tested for correlation with the Pearson correlation test obtained results of 0.62 with a significance of 0.0641 < 0.05 ie there is a strong relationship between student Self-Efficacy with student achievement index or it can be mentioned that there is no significant relationship between Self-Efficacy with the academic achievement index of Faculty of Teacher Training and Education at the Malikussaleh University in the 2018/2019 academic year.